Cost‐effectiveness analysis of the atraumatic restorative treatment‐based approach to managing early childhood caries. Issue 1 (14th November 2016) - Tonmukayakul, Utsana; Arrow, Peter
Abstract: Objective: Paediatric dental care under general anaesthesia among preschool children in Western Australia is increasing and costly. This study assessed cost‐effectiveness of the atraumatic restorative treatment‐based (ART‐based) approach against the standard care (SC) approach to managing early childhood caries in a primary care setting based on a 1‐year pragmatic randomized controlled trial. Methods: Cost‐effectiveness analysis, from the service provider perspective, was conducted. Outcomes include number of referral to specialists and dental treatments. One‐way and probabilistic sensitivity analyses were undertaken to test the robustness of the cost‐effectiveness estimates. Results: Six children in the ART‐based group and 62 children in the SC group ( n = 127 each group) were referred for paediatric dental specialist care. Children in the ART‐based group received more dental services than those allocated to the SC group (mean = 3.8, SD 2.0 and mean = 1.8, SD 1.8, respectively, Wilcoxon rank‐sum test, P < 0.01). Total costs of the ART‐based approach and the SC group were 137 860 and 178 217, respectively. Based on probabilistic sensitivity analysis, 654 was saved per referral to specialist avoided and 36 was saved per additional dental treatment. The probability that the ART‐based approach is cost‐saving was 63%. Specialist dental treatment fees had a big impact on the cost‐effectiveness estimates. Conclusion: The ART‐based approach appears to be a worthwhile intervention because it resulted in fewer referred cases and enabled more treatments to be provided with cost‐savings.